2020
DOI: 10.1123/ijspp.2019-0265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Strength and Power Training on Physical Performance and Interlimb Asymmetries in Adolescent Female Soccer Players

Abstract: Purpose: To examine the effects of an 8-week combined strength and power training intervention on physical performance and interlimb asymmetries in adolescent female soccer players. Methods: Thirty-seven adolescent female soccer players (age 16.1 [1.1] y) were randomly assigned to a control group (n = 18) or experimental group (n = 19). The experimental group performed combined strength and power training twice a week, which consisted of strength and power exercises that trained the major muscles of the lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 42 publications
(56 reference statements)
9
42
4
1
Order By: Relevance
“…The selected studies were submitted to the PEDro methodological quality scale. Two studies obtained a score of 9/10 [ 36 , 37 ], one study obtained 8/10 [ 38 ], six obtained 7/10 [ 5 , 6 , 39 , 40 , 41 ], two obtained 5/10 [ 42 , 43 ], and two obtained 4/10 [ 44 , 45 ]. Table 1 displays the complete and detailed PEDro scale score of each study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The selected studies were submitted to the PEDro methodological quality scale. Two studies obtained a score of 9/10 [ 36 , 37 ], one study obtained 8/10 [ 38 ], six obtained 7/10 [ 5 , 6 , 39 , 40 , 41 ], two obtained 5/10 [ 42 , 43 ], and two obtained 4/10 [ 44 , 45 ]. Table 1 displays the complete and detailed PEDro scale score of each study.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to observe the between-mode analysis due to the comparison between the same ST or PT group (intra-group), whilst within-mode analysis is a comparison between EG and CG of ST or PT training and, occasionally, this mode of analysis does not represent the reality of the results. In this sense, Pardos-Mainer et al [ 5 ] demonstrated a large effect (ES = −1.17) in linear sprint performance after an ST which is combined with power exercises. Similar results have been found by Ozbar et al [ 42 ] (ES = −1.12) after a PT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations